Charging and discharging methods of lead acid battery - Muhamad Syafiq, Kadiran (2012)
Battery has played a major in many applications such as electric vehicle and uninterruptable power supply (UPS). Battery becomes a must choice because it can provide immediate power when needed. Among the battery family, lead-acid battery become a popular choice because it came in variety of output voltage and can be recharge. Although the lead-acid can be recharge, problems still occur when recharging the battery. The battery tend to undergo overcharge if the is no control mechanism to stop the charging. This paper represents a method of charging and discharging the battery by using electronic control circuit based on the minimum and maximum voltage battery level. A NI-DAQ 6212 was introduced and configures to connect the electronic control circuit to the personal computer for display and data storage using LabVIEW. A charge and discharge program was developed to use for charging and discharging purpose. The output of this project would be displaying the voltage-time graph as well as the charging and discharging state of the lead-acid battery.